Analisis Yuridis Penjatuhan Pidana terhadap Anak Pelaku Pidana yang Diancam dengan Ketentuan Pidana yang Memiliki Ketentuan Ancaman Minimal Khusus - Samuel Saut Martua Samosir (JURNAL RECHTENS, 2014)
One of the criminal provisions that have specific minimum criminal sanctions and can only be done by a child actor is the provision referred to in Article 81 of Law No. 23 of 2002 on the Protection of the Child which states that any person who knowingly commit violence or threats of violence to force children sexual intercourse with him or with another person, shall be punished with imprisonment of fifteen (15) years and a minimum of 3 (three) years ....., but the laws of the criminal justice system in addition to providing kakhususan for child actors, namely as under the provisions of 81, paragraph 2 of Law criminal Justice System Child which states that imprisonment can be imposed on the longest Son 1/2 (one half) of a maximum penalty of imprisonment for adults, it is based on the principle of lex specialis derogat legi generali, rules general no longer have the force of law when there are specific rules, which in this case is the set of criminal punishment for child offenders.